A meta-analysis of the haemodynamics of primary hypertension in children and adults. Issue 2 (2nd February 2023) - Li, Ye; Haseler, Emily; McNally, Ryan; Sinha, Manish D.; Chowienczyk, Phil J.
Abstract : We performed a systematic review and meta-analysis to determine the relative contributions of elevated cardiac output and systemic vascular resistance to hypertension in children and adults. This included 27 studies on 11 765 hypertensive and normotensive children and adults in whom cardiac output was measured. Cardiac output but not systemic vascular resistance was elevated in hypertensive compared to normotensive children and young adults (difference in means 1.15 [0.78–1.52] l/min, P < 0.001). In older hypertensive adults, both were elevated compared to normotensive individuals (0.40 [0.26–0.55] l/min, P < 0.001 and 3.21 [1.91–4.51] mmHg min/l, P < 0.001 for cardiac output and systemic vascular resistance, respectively). The main haemodynamic alteration in primary hypertension (including obesity-hypertension) in both children and young to middle-aged adults is an elevation of cardiac output. With longer duration and greater severity of hypertension there may be progression from a 'cardiac' to a 'vascular' phenotype with increased systemic vascular resistance.